(untitled) (Research, Society and Development, 2022)
Cheeses are dairy products that provide various nutritional health benefits to consumers in addition to their economic importance. Cheese consumption, however, is under increasing scrutiny due to health risks associated with cytotoxins that could potentially be generated during processing or maturation due to physicochemical or microbiological changes. In addition to the health risk, spoilage changes lead to a large economic loss. The objective of this paper is to report on the main microbiological contaminations and lipid oxidation alterations that affect the quality of cheeses sensorially and nutritionally. The artisan cheeses are those most subject to microbiological contaminations due to poor hygienic conditions. Several pathogenic microorganisms can contaminate the cheeses and produce disease-causing or even fatal toxins if the hygiene has not been done in a heated way and does not respect the Good Manufacturing Practices. Failure in storage can cause lipid oxidation in cheeses resulting in toxic products.